Emotional control of kindergarten teachers (Journal of the College of Basic Education, 2023)
The aim of the current research is to identify the emotional control of kindergarten teachers. The research relied on the descriptive approach, and the research sample was (400) teachers from the directorates of education in Baghdad / Karkh side (Karkh the first _ Karkh the second _ Karkh the third). After examining the theories and previous studies on the subject of the research, the emotional control scale in its final form included (35) items. The two researchers verified the psychometric characteristics of the tool. The following results were reached:Kindergarten teachers have emotional control